2019
DOI: 10.12911/22998993/108700
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Chlorophyll-a and Its Relationship with Dissolved Inorganic Phosphate Influenced by Rivers in the North Coast of Java

Abstract: This research examines the eutrophication process mainly by considering the chlorophyll-a concentration. A simple linear model was used to determine the correlation between Chlorophyll-a and dissolved inorganic phosphate (DIP). The research was carried out on river mouths in the north coast of Central Java. The results of the linear model show that the relationship between chlorophyll-a and DIP follows the logarithmic model with the log [Chloa] = 1.52 + 1.60 log [DIP], R 2 = 0.55. The model suggests that the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 20 publications
2
36
1
5
Order By: Relevance
“…37 It is known that the concentration of chlorophylla is related to inorganic phosphate concentrations and the Pearson Correlation Index result positive correlation between phosphate and chlorophyll-a support it. 38 The value of Kelly index (KI) is less than 1 in all stations and the water is suitable for irrigation (Table S-I). With respect to the sodium adsorption rate (SAR), the value is between 0-10 in all stations and the results show that the water is excellent for irrigation (Table S…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…37 It is known that the concentration of chlorophylla is related to inorganic phosphate concentrations and the Pearson Correlation Index result positive correlation between phosphate and chlorophyll-a support it. 38 The value of Kelly index (KI) is less than 1 in all stations and the water is suitable for irrigation (Table S-I). With respect to the sodium adsorption rate (SAR), the value is between 0-10 in all stations and the results show that the water is excellent for irrigation (Table S…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Dampak positif terjadi karena produktivitas perairan menjadi tinggi, sedangkan dampak negatif akibat proses eutrofikasi yang menyebabkan algae jenis beracun berkembang dengan pesat dan menyebabkan oksigen perairan menjadi rendah. Hasil penelitian Maslukah et al (2019) tentang unsur phosphat terlarut di perairan Semarang mencapai 0,52 µM dan Jepara 0,36 µM. Beban masukan ion P yang cukup tinggi telah menyebabkan konsentrasi klorofil-a menjadi lebih tinggi dibanding dengan perairan Jepara.…”
Section: Pendahuluanunclassified
“…Maslukah et al (2018) explained that chlorophyll a in Jepara waters had the strongest correlation to the N/P ratio, followed by P and finally N individually. The following study, Maslukah et al (2019), found a relationship of chlorophyll a to nutrient P following a logarithmic model with the formula [Chl-a] = 1.52 + 1.60 logs [P], with a correlation coefficient (r) of 0.74. A comprehensive model of this relationship that can be applied to waters with different characteristics would be very valuable to develop effective policies to control the water quality (Abell et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This region has experienced very rapid development because it is the main center of economic growth in Central Java. Several studies related to the chlorophyll a concentration have been carried out by Siregar and Koropitan (2016), Subiyanto et al (2017) and Maslukah et al (2019). The concentration of the particulate P forms in waters is rarely measured.…”
Section: Introductionmentioning
confidence: 99%